2019
DOI: 10.5005/jp-journals-10024-2559
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study Comparing Fracture Resistance of Nanocomposites with and without Fiber Reinforcement with Different Cavity Designs Used for Obliquely Fractured Incisal Edge Restoration

Abstract: Aim:The aim of the study is to evaluate fracture resistance of nanocomposites with and without fiber reinforcement with different cavity designs used for obliquely fractured incisal edge restoration. Materials and methods: In the present study, 60 sound extracted maxillary central incisors were mounted on autopolymerizable acrylic resin up to the cementoenamel junction, out of which, 10 intact teeth were kept as control (group 1) and the remaining 50 samples were reduced incisally in an oblique manner up to 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, in contrast to the common perception, in a study conducted by Gayatri et al, a single ribbond fiber showed more fracture resistance as compared to two fibers. 33 Also Sharafeddin et al 31 discovered that samples with two fibers in two slots had lower fracture resistance than single fiber samples. Because a centrally located fiber is closer to the long axis of the tooth, it appears to distribute forces equally across a wider area of the tooth, however, when it is placed farther from the center, the force is dispersed unevenly to other parts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the common perception, in a study conducted by Gayatri et al, a single ribbond fiber showed more fracture resistance as compared to two fibers. 33 Also Sharafeddin et al 31 discovered that samples with two fibers in two slots had lower fracture resistance than single fiber samples. Because a centrally located fiber is closer to the long axis of the tooth, it appears to distribute forces equally across a wider area of the tooth, however, when it is placed farther from the center, the force is dispersed unevenly to other parts.…”
Section: Discussionmentioning
confidence: 99%